THE USE OF SINGLE PICTURES AS A MEDIA TO TEACH WRITING DESCRIPTIVE TEXT TO THE SEVEN GRADERS OF SMP ANGELUS CUSTOS II KEBRAON, SURABAYA (RETAIN, 2015)
Abstract Writing is a skill to enable the students to communicate in written. Besides, writing has much a difficulties process which is make the students who study English get difficulty because they have low mastery of vocabulary. The other problems are teaching method and environments are the main cause of students’ weaknesses in writing English and students’ difficulties in tenses. Based on those problems, the teacher can use single pictures as the alternative and interesting media in teaching writing. Single Pictures is an interesting media for teaching students in writing class. The aim of this research is to describe the implementation of single pictures to teach writing descriptive text taught by the teacher and to describe the students’ attitude toward the use of single pictures. The data of this study are obtained from the result of unstructured field notes and the result of questionnaire. The results of this study realize that the implementation of single pictures encourages the students to increase their vocabulary in writing descriptive text. In addition, the number of students’ bored on reduces through this media. It means that students feel interested in the implementation of single pictures. In conclusion, single pictures is a good and interesting media to be used in teaching writing descriptive text, especially for the seven graders, since it helps the students to solve their problems above in writing, stimulate the students’ creativity, and create an interesting atmosphere in the class. Kata Kunci: single pictures, teaching writing, descriptive text Abstrak Menulis adalah suatu keterampilan yang dapat memampukan siswa berkomunikasi dalam tulisan. Selain itu, menulis memiliki sangat banyak kesulitan dalam proses penulisan yang membuat siswa yang belajar bahasa inggris menjadi sulit karena mereka memiliki penguasaan kosakata yang rendah. Masalah yang lain adalah metode pengajaran dan lingkungan adalah merupakan masalah yang utama dari kelemahan siswa dalam menulis bahasa inggris dan kelemahan siswa dalam tenses. Berdasarkan masalah-masalah itu, guru dapat menggunakan single pictures sebagai media cadangan dan menarik dalam pengajaran menulis. Single Pictures adalah suatu media yang menarik untuk mengajar siswa dalam kelas menulis di pelajaran bahasa inggris. Tujuan dari penelitian ini adalah untuk medeskripsikan dari penggunaan single pictures untuk mengajar menulis deksriptif teks yang diajarkan oleh guru dan untuk mendeskripsikan sikap siswa terhadap penggunaan single pictures sebagai media untuk mengajar menulis deksriptif teks pada kelas tujuh. Data dari studi ini diperoleh dari hasil unstructured field notes dan hasil questionnaire. Hasil dari studi ini menyadari bahwa penerapan single pictures mendorong siswa-siswa untuk meningkatkan kosakata mereka dalam menulis deksriptif. Sebagai tambahan, angka kebosanan siswa dapat menurun melalui media ini. Itu menyimpulkan bahwa siswa-siswa merasa tertarik dalam penerapan dari single pictures. Secara kesimpulan, single pictures adalah media yang bagus dan menarik untuk digunakan dalam pengajaran menulis deksriptif teks, khususnya untuk kelas tujuh, selama itu dapat membantu siswa-siswa untuk mengatasi masalah-masalah mereka dalam menulis, merangsang kreatifitas siswa-siswa, dan menciptakan atmosfir yang menarik di dalam kelas. Key Words: single pictures, teaching writing, descriptive text